Drying Simulation of Rough-Rice in a Horizontal-Semi Cylindrical Plenum (Drying-Bed) - Atjeng M. Syarief (PERTETA, 2001)
Simulation technique was used to determine the drying charaden'stic of roughrice in a horizontal-semi cylindrical plenum (drying-bed). The mathematical model simulation used in study was a set of partial d&rential equation. In order to ve*the validity of the simulation technique, the experimental tests were tun to provide data to he compared with the simulation results. The experimentation was conducted using rough-rice samples at two levels of drying temperatures, 50% and45%. The results indicate that the mathematical model predicts the charactetkiics of the actual rough-rice dtying very closely that the differences are staWicaUy no significant, although there are little bit (=95%) differem between the simulatitmtechnique and the test run results. These are true not only for the drying air temperature data but also for the moisture content data as well.